Marginal prices of improvements made to blocks of flats: empirical evidence from Romania - Deaconu, Adela; Lazar, Dorina; Buiga, Anuta; Fatacean, Gheorghe (International Journal of Strategic Property Management, 2016)
This paper examines a specific segment of the housing markets from Central and Eastern European countries, namely the stock of flats in the urban area. With focus on Romania, we emphasize the improvements made by owners and authorities, aimed to enhance the quality of life and the maintenance of old blocks of flats; are highlighted some aspects regarding the cost of these improvements. In addition, the empirical section investigates whether and to what extent the improvements made to the flats and buildings have a significant effect on sale prices and rental prices. The marginal prices of these attributes are provided by hedonic pricing models, estimated in a generalized linear model framework; gamma and log-linear regression models perform in a similar way in terms of fit and prediction accuracy. The physical condition of the building and finishing works inside the flats, as variables of interest in our models, have a significant effect on sale and rental prices, but with different intensity. A common set of significant attributes, in the hedonic models for both sale and rental price, is suggested.